Crystallographic Structural and Magnetic Properties of FePt Nanoparticles - Van, Nguyen Thi Thanh; Trung, Trương Thanh; Nam, Nguyen Hoang; Luong, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics, 2014)
Abstract: Fe 60 Pt 40 nanoparticles have been successfully prepared by sonochemistry method from the solution of Fe(C 2 H 3 O 2 ) 2 and H 2 PtCl 6 . The as-prepared sample then has been annealed at temperatures from 450 o C to 650 o C. Annealed samples have ordered L1 o phase with face-centered tetragonal (fct) structure and show hard magnetic properties. The nanoparticles annealed at 550 o C show highest coervicity of 4.36 kOe measured at room temperature. The annealed-temperature dependence of the coercivity is consistent with the appearance of the order phase L1 o in the samples. Keywords: FePt nanoparticles, coercivity, squareness, annealing temperature, sonochemistry.